Principles of Introducing the Institution of Mediation in Public Legal Disputes in Ukraine - K. S. Tokarieva (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on theoretical study of the principles of introduction of the institution of mediation in public law disputes in Ukraine. It has been determined that the introduction of mediation in the field of public administration should be carried out in accordance with the specifics of public law disputes. The current status of legal regulation of mediation in Ukraine has been analyzed. It has been emphasized that the main way to introduce the institution of mediation in resolving public law disputes is to create and continuously improve the administrative and legal regulation of mediation. The emphasis has been placed on the great influence of the principles of the mediation procedure on further formation of legal regulation of mediation. The article is focused on theoretical study of the principles of legal regulation of mediation as an element of the content of administrative and legal regulation of the social and legal institution of mediation, it considers scientific approaches to the concept of administrative and legal regulation and forms of its own definition. Administrative and legal regulation of mediation in the study has been understood as the purposeful influence of the state, its agencies and officials on relations arising in the field of mediation, in order to achieve stability, law and order through the use of legal means (legal norms, legal principles, legal facts, etc.) for establishing the extent of possible and necessary behavior of mediation subjects. The article illustrates the division of principles as legal means of administrative and legal regulation of mediation into general and special ones. The general principles of regulation of mediation in the administrative process correspond to the principles of administrative law. The basic principles of such regulation are the principles of the rule of law, legality, justice, priority of human and civil rights and freedoms, humanism, equality, non-discrimination, responsibility of the individual and the state, publicity, compliance with international standards, minimum state intervention, proportionality, etc.; the essence of each principle has been also clarified. Further research on the issues of the scientific article should be aimed at the possibility of practical application, implementation and realization of the principles of administrative and legal regulation of mediation.